Broadband High-Selectivity Stacked Filtering Antenna with Multiple Radiation Nulls - Shuai Gao; Zhongbao Wang; Hongmei Liu; Shaojun Fang (Journal of Microwaves, Optoelectronics and Electromagnetic Applications)
Abstract In this paper, a novel broadband high-selectivity stacked filtering antenna with multiple radiation nulls is proposed. The antenna consists of a short-circuited stepped impedance feeding line and two U-shaped strips on the bottom layer, four parasitic patches and a rectangular driven patch etched with two Г-shaped slots on the top layer. Short-circuited stepped impedance feeding line and Г-shaped slots respectively introduce two radiation nulls, which greatly improves low-band edge selectivity. Two U-shaped strips and four parasitic patches respectively introduce two radiation nulls, effectively increasing the upper stopband rejection level. For demonstration, one prototype of the filtering antenna with a center frequency of 2.4 GHz is fabricated and measured. Measurement results manifest that the impedance bandwidth is 15.8% (from 2.18 to 2.56 GHz) with the antenna gain of 7.69 dBi. Furthermore, four radiation nulls can be generated at 1.91, 2.01, 2.60, and 2.72 GHz, respectively. And the lowerand upper-edge selectivities are 157.3 and 310.9 dB/GHz, respectively.